2022
DOI: 10.3390/nu14153154
|View full text |Cite
|
Sign up to set email alerts
|

SARC-F Is a Predictor of Longer LOS and Hospital Readmission in Hospitalized Patients after a Cardiovascular Event

Abstract: It is already established that sarcopenia is associated with adverse outcomes; however, few studies have focused on patients who have suffered an acute cardiovascular event. The use of SARC-F, a 5-item sarcopenia screening questionnaire, in these patients remains to be investigated. We aimed to investigate whether SARC-F can predict adverse outcomes in patients admitted to a hospital with a suspected infarction. This is a 1-year prospective cohort study. During hospitalization, patients completed the SARC-F qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…22 Mori et al 23 showed SARC-F as a practical predictor of prognosis for cancer patients who were receiving palliative care. Trussardi Fayh et al 24 presented its association with a longer length of stay and hospital readmission after a cardiovascular event. Another important study was conducted by Bahat et al, 25 who showed the predicting capacity of SARC-F to define frailty.…”
Section: Discussionmentioning
confidence: 99%
“…22 Mori et al 23 showed SARC-F as a practical predictor of prognosis for cancer patients who were receiving palliative care. Trussardi Fayh et al 24 presented its association with a longer length of stay and hospital readmission after a cardiovascular event. Another important study was conducted by Bahat et al, 25 who showed the predicting capacity of SARC-F to define frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the substantial impact of skeletal muscle abnormalities on the prognosis of cardio-cerebrovascular disease, malignancy and even the all-cause mortality in the general population [4][5][6][7]. At present, the role of muscle alterations on the development and outcomes of chronic liver diseases also becomes a major concern of the hepatologists [8,9].…”
Section: Introductionmentioning
confidence: 99%